2012
DOI: 10.1111/mec.12137
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and in vivo tests reveal novel mechanisms underlying endocrine disruption in an ecological sentinel, Nucella lapillus

Abstract: Anthropogenic endocrine disruptors now contaminate all environments globally, with concomitant deleterious effects across diverse taxa. While most studies on endocrine disruption (ED) have focused on vertebrates, the superimposition of male sexual characteristics in the female dogwhelk, Nucella lapillus (imposex), caused by organotins, provides one of the most clearcut ecological examples of anthropogenically induced ED in aquatic ecosystems. To identify the underpinning mechanisms of imposex for this 'nonmode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 63 publications
1
44
0
1
Order By: Relevance
“…In gastropods, exposure to TBT causes irreversible superimposition of male genital on females, a condition termed imposex, whilst in bivalve species, exposure to TBT causes growth reduction [3032], and shell thickening [3336]. The mechanism by which TBT affects mollusc species remains unclear, although hypotheses have been raised related to binding to and disruption of a putative molluscan RXR or RXR/peroxisome proliferator-activated receptor (PPAR) heterodimer [29, 3747]. …”
Section: Introductionmentioning
confidence: 99%
“…In gastropods, exposure to TBT causes irreversible superimposition of male genital on females, a condition termed imposex, whilst in bivalve species, exposure to TBT causes growth reduction [3032], and shell thickening [3336]. The mechanism by which TBT affects mollusc species remains unclear, although hypotheses have been raised related to binding to and disruption of a putative molluscan RXR or RXR/peroxisome proliferator-activated receptor (PPAR) heterodimer [29, 3747]. …”
Section: Introductionmentioning
confidence: 99%
“…Chemical contaminants with estrogen receptor agonist or androgen receptor antagonist activity are present in wastewater effluents (Hill et al, 2010;Sumpter and Jobling, 2013) and studies to date have indicated that the steroidal estrogens and possibly anti-androgens present in the receiving waters are causing the high levels of feminized fish present in some UK river sites (Jobling et al, 2006(Jobling et al, , 2009. Other EDCs such as organotins, which in the past were used in marine antifouling paints, have caused widespread masculinization of female gastropods and may act as ligands for different nuclear receptors involved in sexual differentiation rather than those for sex steroids (Pascoal et al, 2013;Titley-O'Neal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing transcriptome responses in laboratory-reared animals exposed to water or sediment obtained from the field is an increasingly common method used in environmental assessments [4,[28][29][30][31][32]. Although sediment brought into the laboratory more accurately reflects the complex mixtures present in situ, it should not be considered field-based, and these studies are not further considered in the present review.…”
Section: Transcriptomic Field-based Studiesmentioning
confidence: 99%